Adsorption of CO molecules on anatase TiO2(001) loaded with noble metals M (M = Ir/Pd/Pt): A study from DFT calculations. (September 2021) - Shi, Zhengguang; Lin, Long; Chen, Ruixin; Yan, Longbin
Abstract: The structure and electronic behaviour of anatase TiO2 (001) surface loaded with noble metal atoms M (Ir, Pd and Pt) are systematically investigated by first-principles calculations. Meanwhile, the adsorption behaviour of CO on M-loaded anatase TiO2 is also studied. The results show that Ir and Pt atoms are more likely to be adsorbed on the O2 C (T1) site, while Pd atom is more easily adsorbed at the Ti5 C (T3) site. Among all of the considered systems, the formation energy of Pd/TiO2 (−2.500 eV) is the lowest one followed with Pt/TiO2 (−4.552 eV) and Ir/TiO2 (−6.298 eV). The adsorption mechanism of CO on the anatase TiO2 (001) surface is studied by choosing the most stable configurations. The order of adsorption energy is CO/TiO2 (−1.065 eV) >CO/Pd/TiO2 (−2.535 eV) >CO/Pt/TiO2 (−3.326 eV) >CO/Ir/TiO2 (−3.593 eV). This theoretical study shows the adsorption mechanism of CO on the anatase TiO2 (001) and provides guidelines for further exploring the adsorption material with excellent adsorption capacity. Graphical Abstract: ga1